The perils of Lady Catherine de Bourgh - Gray, Claudia (Gray, Claudia. Mr. Darcy & Miss Tilney mystery., 2024)
"The third book in the Mr. Darcy & Miss Tilney Mystery series, which finds the amateur sleuths facing their most daunting challenge yet: preventing the murder of the imperious Lady Catherine de Bourgh. Someone is trying to kill Lady Catherine de Bourgh. Esteemed aunt of Mr. Fitzwilliam Darcy, generous patroness of Mr. William Collins, a woman of rank who rules over the estate of Rosings Park with an unimpeachable sense of propriety-who would dare? Lady Catherine summons her grand-nephew, Mr. Jonathan Darcy, and his investigative companion, Miss Juliet Tilney, to find out. After a year apart, Jonathan and Juliet are thrilled to be reunited, even if the circumstances-finding whoever has thus far sabotaged Lady Catherine's carriage, shot at her, and nearly pushed her down the stairs-are less than ideal. Also less than ideal: their respective fathers, Mr. Fitzwilliam Darcy and Mr. Henry Tilney, have accompanied the young detectives to Rosings, and the two men do not interact with the same felicity enjoyed by their children. With attempts against Lady Catherine escalating, and no one among the list of prime suspects seemingly capable of committing all of the attacks, the pressure on Jonathan and Juliet mounts-even as more gentle feelings between the two of them begin to bloom. The race is now on to provoke two confessions: one from the attempted murderer before it is too late-and one, perhaps, of love"--